Discussion on the Application of Computer Digital Technology in the Protection of Intangible Cultural Heritage. Issue 3 (May 2021) - Shuai, He; Yu, Wu
Abstract: With the globalization of global economy, the protection of intangible cultural heritage is facing a crisis of survival. Intangible cultural heritage is the crystallization of the wisdom of the working people of a country in past dynasties, with strong national characteristics. Applying digital technology to the protection of intangible cultural heritage can promote the inheritance, transformation and application of intangible cultural heritage. Since China put forward the information development strategy, it has become more practical to use digital technology to protect cultural heritage. Due to the imperfection of management mechanism and format specification, as well as the special nature of intangible cultural heritage, the development of digital means is still very difficult. In order to better protect the digital technology, this paper studies the important role of digital technology in the protection and inheritance of intangible cultural heritage, and further studies the deep development and application of digital technology in the protection and inheritance of intangible cultural heritage.